Kisah Cinta Platonik Jalâl al-Dîn al-Rûmî - Alfi Jihad, Zayyin (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2011)
The research attempts to discover and find the very roots of love concept by Jalâl al-Dîn Rûmî to develop Sufism method, which connects human?s hearts with their God. This study employs philosophical qualitative method, which tends to be descriptive and interpretative. Using the basis of love, Jalâl al-Dîn Rûmî built sufistic epistemological foundation in the form of mystical poems. Poems are means of spiritual pilgrimage, which is performed in order to find the culmination of fusion ectacy between human and their God, i.e. Allah The Almighty.